Development of norms for executive functions in typically-developing Indian urban preschool children and its association with nutritional status. Issue 2 (17th February 2018) - Selvam, Sumithra; Thomas, Tinku; Shetty, Priya; Thennarasu, K.; Raman, Vijaya; Khanna, Deepti; Mehra, Ruchika; Kurpad, Anura V.; Srinivasan, Krishnamachari
ABSTRACT: Executive functions (EFs) are essential and important for achieving success in children's everyday lives and play a fundamental role in children's cognitive, academic, social, emotional and behavioral functioning. A cross-sectional study was carried out to develop age- and sex-specific norms for EFs using the Behavior Rating Inventory of Executive Function – Preschool Version (BRIEF-P) among 2- to 5-year-olds from urban Bangalore, India. In addition, the association between EFs and anthropometric measures, a marker of nutritional status, is also examined. Primary caregivers of 412 children, equally distributed by age and sex, participated. Raw scores for each domain and indices were converted to standard t -scores and percentiles were computed. A t -score at or above 63 corresponding to the 90th percentile was considered as the cutoff for executive dysfunction in this sample. The prevalence of executive dysfunction is 10% based on the Global Executive Composite score of the BRIEF-P. The cutoff score for identifying executive dysfunction using existing United States (US) norms is higher compared to the cutoff score obtained in the current study. Therefore, using US norms for Indian children could result in the prevalence of executive dysfunction been underestimated. Multiple linear regression analysis revealed that stunted and underweight children have significantly elevated EF scores after adjusting for age, sex and socioeconomic status (SES; p < .01). A greater understanding of EFs in preschool children is important for the early identification of executive dysfunction and implementing interventions to improve their future prospects. This study also shows that undernourished children are more likely to have executive dysfunction.